The Association between Corporate Governance and Auditor Switching Decision - Abidin, Shamharir; Ishaya, Ishaku Vandi; M-Nor, Mohamad Naimi (International Journal of Economics and Financial Issues, 2016)
The purpose of this study is to examine the association between corporate governance and the propensity of auditor switching. In particular, the study seeks to investigate whether board independence and Chairman-CEO duality, influence the auditor-client realignment exercise. Understanding the reasons why companies switch auditor is very important as auditor switching could inhibit the flow of capital in the securities markets, and subsequently, increase the capital costs. Based on the analysis of 712 non-financial companies listed on Bursa Malaysia during the period from 31st December, 2009 to 2011, the results suggest that the companies with higher non-executive directors than the sample median tend to switch auditor. The Chairman-CEO duality, however, has no effect on the decision. The results also suggest that the provision of non-audit service, changes in key management, company size and Big 4 are significant determinants of auditor switch decision. The outcome of the study indicates the importance of sound governance on auditor switch decision and might provide insightful knowledge which helps shareholders to realize the importance of having balance BODs. Keywords: Auditor Switch, Audit Market, Auditor Change, Corporate Governance, Malaysia JEL Classifications: M41, M43, M49